SYNTACTIC STYLISTIC DEVICES: A DEEP DIVE INTO SYNTACTIC STYLISTICS - Abduraxmanova Zilola; Urinboev Shakhzod; Butabekova Durdona (Лучшие интеллектуальные исследования, 2023)
Annotation: This comprehensive article explores the realm of "Syntactic Stylistic Devices," shedding light on the artistry inherent in language manipulation. From inversions and parallelism to anaphora and chiasmus, the piece delves into various syntactic devices employed by writers to elevate their language from mere communication to an expressive art form. Through a structured examination of each device, readers gain insights into the profound impact these techniques have on the aesthetic appeal, rhythm, and emotive power of written expression. The article serves as a valuable resource for writers, linguists, and language enthusiasts seeking to unravel the intricacies of syntax in literary and rhetorical contexts.